Diversity of Mollusc in the Pandan Beach, Tapanuli Tengah Regency, North Sumatera Province - Harahap, Asmul Fauzi; Putra, Ridwan Manda; ', Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Pandan Beach is inhabit by marine organisms, including mollusc. A research aims to determine species types and diversity of mollusc in the Pandan Beach was conducted on December 2015. Mollusc samples were collected 2 times from 3 stations. In each station, 5 quadrans (1x1 m) were placed randomly and mollusc present inside the quadrans were removed. The mollusc captured were identified based on Abott (1991) There were 17 mollusc species present, 7 species Bivalves and 10 species Gastropodes. The most common species was Saturnia corpulenta (The Important Value Index 59.45%). The rarest species was Daphanella elata, Polinices helicoides, Acteocina caniliculata, Fulgurofosus grabau, Tapes itterata. The diversity index (H’) ranged from 1.912 – 2.680, the evenness index (E) was 0.274 – 0.389, the dominant index (C) was 0.276 – 0.999, and the similarity index was 0.35 – 0.61. Based on data of obtained, it can be concluded that the Pandan Beach is suitable to support the live of mollusc.Keyword : Saturnia corpulenta, mollusc diversity, Pandan Beach